Ball Handling Practice Survey on Basketball Dribbling Ability with Application of Relevant Theory - Budiyanto, Rizki Arif; Rosani, Meilia; Putri, Siti Ayu Risma (Yayasan Sembilan Pemuda Indonesia, 2023)
Ball Handling is an important technique for achieving increasing basketball dribbling technique training. One of the things that must be done by every athlete in developing and improving sports performance optimally is by diligently practicing, with exercises that must be developed and improved to master basic techniques. The purpose of this study was to determine ball handling exercises on basketball dribbling abilities. This study uses a literature review research method using 16 literature sources, 12 of which are used as data reviewed and taken from nine databases (Google Scholar, UNP Journal, Research Article, Garda Portal, Sinta ristekbrin, JOSSAE) which demonstrate ball handling exercises. The conclusion in ball handling exercises is that there is a need for each according to the sample level examined by previous relevant studies with ball handling exercises that can improve basketball dribbling skills. In designing the training program must be structured.